UBE2S and UBE2C confer a poor prognosis to breast cancer via downregulation of Numb - Guo, Yanjing; Chen, Xinyu; Zhang, Xiaowei; Hu, Xichun (Frontiers in Oncology, 2023)
Purpose: Ubiquitin-conjugating enzyme E2S (UBE2S) and ubiquitin-conjugating enzyme E2C (UBE2C), which mediated the biological process of ubiquitination, have been widely reported in various cancers. Numb, the cell fate determinant and tumor suppressor, was also involved in ubiquitination and proteasomal degradation. However, the interaction between UBE2S/UBE2C and Numb and their roles in the clinical outcome of breast cancer (BC) are not widely elucidated. Methods: Oncomine, Cancer Cell Line Encyclopedia (CCLE), the Human Protein Atlas (HPA) database, qRT-PCR and western blot analyses were utilized to analyze UBE2S/UBE2C and Numb expression in various cancer types and respective normal controls, breast cancer tissues and breast cancer cell lines. The expression of UBE2S/UBE2C and Numb in BC patients with different ER, PR and HER2 status, grades, stages and survival status were compared. By Kaplan-Meier plotter, we further evaluated the prognostic value of UBE2S/UBE2C and Numb in BC patients. We also explored the potential regulatory mechanisms underlying UBE2S/UBE2C and Numb through overexpression and knocking down experiments in BC cell lines, and performed growth and colony formation assays to assess cell malignancy. Results: In this study, we showed that UBE2S and UBE2C were overexpressed while Numb was downregulated in BC, and in BC of higher grade, stage and poorer survival. Compared to hormone receptor negative (HR-) BC cell lines or tissues, HR+ BC demonstrated lower UBE2S/UBE2C and higher Numb, corresponding to better survival. We also showed that increased UBE2S/UBE2C and reduced Numb predicted poor prognosis in BC patients, as well as in ER+ BC patients. In BC cell lines, UBE2S/UBE2C overexpression decreased the level of Numb and enhanced cell malignancy, while knocking down UBE2S/UBE2C demonstrated the opposite effects. Conclusion: UBE2S and UBE2C downregulated Numb and enhanced BC malignancy. The combination of UBE2S/UBE2C and Numb could potentially serve as novel biomarkers for BC.